Assessment of climate characteristics and long-term trends of rainfall and drought in the Congo River Basin. Issue 11 (10th October 2022) - Mabrouk, Eman Hassan; Moursy, Fawzia Ibrahim; Morsy, Mostafa
Abstract: This study aims to assess patterns, variability, and trends of rainfall and meteorological drought and identify the different climatic zones using 42-year monthly TerraClimate gridded precipitation data at 23 sites distributed to cover the entire Congo River Basin. The spatial distribution of seasonal rainfall and the Köppen climate classifications indicated that the Congo River Basin has three main climatic zones. Where the highest rainfall is received in zone A (north of 2.5°N) during June–August (JJA), in zone B (3.5°S–2.5°N) during March–May (MAM) and September–November (SON), and in zone C (south of 3.5°S) during December–February (DJF). The Mann–Kendall (M–K) trend analysis of seasonal and annual patterns of rainfall and standardized precipitation drought index (SPI) revealed that there were significant negative trends in most of the three climatic Congo zones except for slight positive trends in small parts within zone C, especially during JJA, which are found sometimes in zone B. Finally, the three Congo climatic zones are characterized by negative trends for seasonal and annual data of both rainfall and the SPI, indicating increased drought risks in the Congo Basin except for small parts in zone C which have positive (wet) trends, especially during JJA followed by DJF. HIGHLIGHTS: Investigate the spatiotemporal characteristics of rainfall over the Congo Basin for 42 years. Assess the long-term variability and trends in rainfall and drought (standardized precipitation index, SPI). Identify the different climatic zones within the Congo Basin based on the spatiotemporal distribution of rainfall and the Köppen-Geiger climate classifications. Graphical Abstract